153 An International Multicenter Matched Cohort Analysis of Incidental Meningioma Progression During Active Surveillance or After Stereotactic Radiosurgery: The IMPASSE Study. (1st April 2022) - Sheehan, Jason P.; Pikis, Stylianos; Islim, Abdurrahman; Mathieu, David; Liscak, Roman; Tripathi, Manjul; Kondziolka, Douglas S.; Bowden, Greg N.; Lunsford, L. Dade; Jenkinson, Michael D.
Abstract : INTRODUCTION: The optimal management of patients with an incidental meningiomas remains unclear. The aim of this study was to characterize the radiologic and neurological outcomes of expectant and SRS management of asymptomatic meningioma patients. METHODS: Using data from 14 centers across 10 countries, the study compares SRS outcomes to active surveillance of asymptomatic meningiomas. Local tumor control of asymptomatic meningiomas and development of new neurological deficits attributable to the tumor were evaluated in the SRS and conservatively managed groups. RESULTS: In unmatched cohorts, 727 meningioma patients underwent SRS and were followed for a mean of 57.2 months. In the conservatively managed cohort, 388 patients were followed for a mean of 43.5 months. Tumor control was 99.0% of SRS and 64.2% of conservatively managed patients (p<0.001; OR 56.860 (95% CI 26.253–123.150)). New neurological deficits were 2.5% in the SRS and 2.8% of conservatively managed patients (p=0.764; OR 0.890 (95% CI 0.416–1.904)). After 1:1 propensity matching for patient age, tumor volume, location, and imaging follow-up, tumor control in the SRS and conservatively managed cohorts was 99.4% and 62.1%, respectively (p<0.001; OR 94.461 (95% CI 23.082-386.568)). In matched cohorts, new neurological deficits were noted in 2.3% of SRS treated and 3.2% of conservatively managed patients (p=0.475; OR 0.700 (95% CI 0.263–1.863)). CONCLUSION: SRS affords superior radiologic tumor control compared to active surveillance without increasing the risk of neurological deficits in asymptomatic meningioma patients. While SRS and active surveillance are reasonable options, SRS appears to alter the natural history of asymptomatic meningiomas including tumor progression in the majority of patients treated.